Finite element method applied to modelling electromagnetic interference and compatibility problems on printed circuit boards. - Khan, Raouf Lawrence. (University of Ottawa (Canada), 1990)
The finite element method is applied to compute the distributed capacitance and inductance matrices for multilayered dielectric, planar transmission media. The analysis involves the solution of the Laplace equation in two dimensions for multiconductor configurations in microstrip, triplate, or TEM Cell configurations of arbitrary cross section and utilizes a unique node allocation algorithm for automatic generation of the finite element mesh. The advantages, disadvantages, and difficulties encountered in application of the FEM for this problem are outlined and discussed. Several programs, based on multiconductor transmission line theory, are developed for application to Electromagnetic Interference and Compatibility (EMI/C) problems for crosstalk and radiated emission analysis. To verify the model experimentally, a simple printed circuit board consisting of five parallel conductors in microstrip configuration was constructed and measured in both time domain and frequency domains. Radiation model results are compared for a multiconductor configuration with numerical results obtained using the Numerical Electromagnetics Code (NEC) moment method program.
Keywords: Engineering, Electronics and Electrical.